2017
DOI: 10.1002/2017jc012822
|View full text |Cite
|
Sign up to set email alerts
|

Formation of sea ice bridges in narrow straits in response to wind and water stresses

Abstract: Ice bridges are rigid structures composed of sea ice that form seasonally in the many straits and channels of the Canadian Arctic Archipelago. Driven primarily by atmospheric stresses, these ice bridges are formed when sufficiently thick ice “jams” during the course of its flow between land masses, resulting in a region of stationary compacted ice that is separated from a region of flowing open water (a polynya) by a static arch. Using a continuum description of sea ice that is widely used in climate modeling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Olason (2016) studied the impact of some physical and numerical parameters of a VP model on the simulated landfast ice in the Kara Sea. Rallabandi et al (2017) developed an analytical theory of the flow of sea ice through narrow straits and on the formation of ice bridges. Dansereau et al (2017) investigated the simulation of ice bridges with the new Maxwell-elasto-brittle rheology.…”
Section: 1029/2018jc014080mentioning
confidence: 99%
“…Olason (2016) studied the impact of some physical and numerical parameters of a VP model on the simulated landfast ice in the Kara Sea. Rallabandi et al (2017) developed an analytical theory of the flow of sea ice through narrow straits and on the formation of ice bridges. Dansereau et al (2017) investigated the simulation of ice bridges with the new Maxwell-elasto-brittle rheology.…”
Section: 1029/2018jc014080mentioning
confidence: 99%
“…In granular materials this behavior is called self‐organized complexity as the overall behavior is governed by the local interactions and the resultant many‐body response of the system (e.g., Bak et al, ). Examples of granular phenomena include jets of sea ice floes in the marginal ice zone (e.g., Feltham, ) and jamming (Herman, ; Kwok et al, ; Rallabandi et al, , ; Samelson et al, ). Mechanical rigidity of granular materials increases with the grain‐packing density.…”
Section: Introductionmentioning
confidence: 99%
“…It can be that the differences tested here are too small to have an noticeable impact; previous modelling experiments 15 in Nares Strait have shown that an sea ice thickness of 4 m drastically changes the circulation (Shroyer et al, 2015). Another possibility is that the Nares Strait circulation is mostly impacted by the formation and flushing of ice bridges (Shroyer et al, 2017), yet accurate formation of such ice bridges in models can only happen for a narrow range of external forcings and strait geometries (Rallabandi et al, 2017). But further studying these questions is however beyond the scope of this paper.…”
Section: Impact On the Ocean Circulationmentioning
confidence: 85%
“…However, because of the large uncertainties connected with the estimations of the sea ice thickness (Kwok, 2005;Kwok et al, 2009), it is hard to determine which thickness is most representative of Nares Strait. This question is made even more complex by the 20 presence of ice bridges, whose implementation in models is an active area of research (Rallabandi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%